Increasing incidence of cancer and stage migration towards advanced disease in children and young adolescents in the Netherlands, 1990–2017. (July 2020) - Reedijk, Ardine M.J.; Kremer, Leontien C.; Visser, Otto; Lemmens, Valery; Pieters, Rob; Coebergh, Jan Willem W.; Karim-Kos, Henrike E.
Abstract: Background: This is the first national study on trends in cancer incidence for children and young adolescents in the Netherlands, including stage at diagnosis as a potential marker of early diagnosis and better staging. Methods: All neoplasms in patients younger than 18 years, diagnosed between 1990 and 2017 ( N  = 15, 233), were derived from the Netherlands Cancer Registry. Incidence rates and the average annual percentage change with 95% CIs were calculated for all cancers combined and diagnostic (sub)groups. The stability of trends was examined by joinpoint analyses. Potential changes in early detection or improved staging over time were evaluated through proportional alterations in stage at diagnosis. Results: The annual overall cancer incidence increased significantly over time by 0.6% (95% CI 0.3–0.8) from 144 per million person-years in 1990–1999 to 162 in 2010–2017 and was significant for both boys (+0.5%, 0.2–0.8) and girls (+0.7%, 0.3–1.1), for infants (aged 0 years; +1.5%, 0.4–2.5), teenagers (aged 10–14 years; +0.6%, 0.3–1.0) and young adolescents (aged 15–17 years; +0.7%, 0.2–1.2), with no trend interruptions. The incidence of leukaemia (+0.7%, 0.3–1.2), malignant CNS tumours including pilocytic astrocytomas (+1.0%, 0.5–1.5), neuroblastoma (+1.2%, 0.1–2.2) and Ewing bone tumours (+2.4%, 0.9–4.0) increased significantly, whereas temporal variation in trends was observed in boys diagnosed with leukaemia, in pilocytic astrocytoma and malignant melanoma. The proportion of early-stage disease increased in patients with testicular germ cell tumours (+21%) and malignant melanomas (+14%), whereas stage migration towards advanced disease was seen for Hodgkin lymphomas, soft tissue sarcomas and medullary thyroid carcinomas. Conclusion: The increasing childhood cancer incidence could not be explained by a rise in early diagnosis, which suggests that background risk factors seem of more importance. Highlights: Annual overall childhood cancer incidence increased over time by 0.6%. Rise in early-stage disease was seen in melanomas and testicular germ cell tumours. More advanced disease seen in Hodgkin, soft tissue sarcomas and thyroid carcinomas. Rise in early diagnosis could not explain the total incidence increase. Risk factors need to be studied to unravel causes behind the incidence increase.